Synthesis, physical-chemical properties and the study of anti-hypoxemic activity of 5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-thion alkylderivatives - V. M. Odyntsova; Ye. S. Pruglo (Zaporožskij Medicinskij Žurnal)
Heterocyclic systems, in particular, 1,2,4-triazole derivatives cause great interest in the development of new medicinal substances for the production of highly effective and safe antihypoxants. This fact has created favorable basis for the synthesis of new alkylderivatives 5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-thion, where R is methyl, phenyl.